Ice Cream Cup Production Using Purple Sweet Potato (Ipomoea batatas L. Poir) as a Substitute Ingredient - Pulungan, Maimunah Hindun; Santoso, E F Sri Maryani (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
AbstractThis study aimed to define the proportion of purple sweet potato addition as a substitute ingredients of the ice cream edible cup and to reduce its baking time. This study was designed using Central Composite Design (response surface method) with 2 factors, i.e. the proportions of purple sweet potato powder and the baking time with water content, cup resistance, and fracturability as the responses. The main component of purple sweet potato ice cream cup is starch and cellulose as shown by the characteristic of the functional group which are C-H of alkene, C= C of alkyna, C = O of aldehyde/ketone/carboxylic acid/ester, C-C group of aromatic ring, C-O alcohol/ether/carboxylic acid/ester, C-H of aromatic ring and C-H of alkene. The result of the study showed that the the optimum proportion of purple sweet potato powder was 75% and the baking time was 45 minutes with the water content of 4.37%, cup resistance of 253.64 minutes, fracturability of 0.2125 N, protein content of 4.79%, and carbohydrate content of 4.66%. Based on the consumer’s acceptance aspect, purple sweet potato ice cream cup was the mostly liked because of its texture and flavor, meanwhile its color and aroma was the mostly disliked.Keywords: baking, central composite design, ice cream cup, purple sweet potatoes AbstrakTujuan penelitian untuk menentukan proporsi penambahan ubi jalar ungu sebagai substitusi pada pembuatan edible cup es krim serta lama waktu pemanggangannya. Penelitian dirancang dengan menggunakan Metode Respon Permukaan Desain Komposit Terpusat (response surface method) dengan 2 faktor berupa proporsi tepung ubi jalar ungu serta lama pemanggangan dengan 3 respon yaitu terhadap kadar air, ketahanan cup, dan daya patah. Komponen utama penyusun cup es krim ubi jalar ungu adalah pati dan selulosa yang ditunjukkan oleh gugus fungsi karakteristik yaitu gugus C-H alkane, C= C alkuna, C = O aldehid/keton/asam karboksilat/ester, gugus C-C cincin aromatik, C-O alkohol/eter/asam karboksilat/ester, C-H cincin aromatik serta C-H alkena. Hasil penelitian menunjukkan bahwa cup es krim terpilih pada proporsi optimal tepung ubi jalar ungu 75% dan lama pemanggangan 45 menit dengan kadar air sebesar 4,37%, ketahanan cup sebesar 253,64 menit, daya patah sebesar 0,2125 N, kadar protein sebesar 4.79%, dan kadar karbohidrat sebesar 4,66%. Penerimaan konsumen cup es krim ubi jalar ungu yang terbaik adalah disukai pada tekstur dan rasa, sedangkan warna dan aroma tidak disukai.Kata kunci: cup es krim, desain komposit terpusat, pemanggangan, ubi jalar ungu